2011
DOI: 10.1111/j.1471-4159.2011.07339.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 mediates dopamine formation in the brain in vivo

Abstract: Cytochrome P450 forms (CYPs) of the brain are thought to play a significance role in maintaining brain homeostasis. They are involved in the metabolism of many endogenous substances such as neurosteroids, monoaminergic neurotransmitters, vitamins and arachidonic acid Funae et al. 2003;Yu et al. 2003;Dutheil et al. 2008).Dopamine is formed in the brain from tyrosine via a classic pathway, however, in vitro studies indicate that it may also be produced via tyramine hydroxylation which is catalyzed by the cDNA-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 68 publications
(135 reference statements)
0
35
0
3
Order By: Relevance
“…Cyp2d9, 2d10, and 2d22 were also detectable in the mouse neuroblastoma cells. CYP2D6 is involved in the metabolism of psychoactive drugs (Toselli et al, 2016) and the biosynthesis of the important neurotransmitters, dopamine and 5-hydroxytryptamine (Bromek et al, 2011;Idle et al, 2003). SH-SY5Y human neuroblastoma cells express CYP2D6, which may play a role in neuroprotection from Parkinson's disease, which generates neurotoxins in the human brain (Mann and Tyndale, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Cyp2d9, 2d10, and 2d22 were also detectable in the mouse neuroblastoma cells. CYP2D6 is involved in the metabolism of psychoactive drugs (Toselli et al, 2016) and the biosynthesis of the important neurotransmitters, dopamine and 5-hydroxytryptamine (Bromek et al, 2011;Idle et al, 2003). SH-SY5Y human neuroblastoma cells express CYP2D6, which may play a role in neuroprotection from Parkinson's disease, which generates neurotoxins in the human brain (Mann and Tyndale, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…63 This study showed that there are sufficient levels of metab olism in the brain to be detected by microdialysis and that this technique may prove to be a useful tool to investigate in vivo brain CYP-mediated metabolism of not only endogen ous neurochemicals, but also of drugs and neurotoxins. Injection of select ive CYP inhibitors into the brain has been used to investigate the mechanism of action of the nonopioid analgesic improgan, and these studies showed that brain CYP epoxygenase activity is required for improgan's analgesic effects.…”
Section: Demonstration Of Brain Cyp Activity In Vivomentioning
confidence: 89%
“…Brain CYPs are inducible, and the organ-and brain-region specificity of induction was found to be quite complex. 7,24,43,45,61 This, with the progressive discoveries that brain CYPs can metab olize endogenous neurochemicals, such as tyramine to dopamine by CYP2D6 62,63 and testosterone to 16α-hydroxytestosterone by CYP2B6, 10,64 lent credence to the idea that these enzymes may play a functional role in the brain in both endogenous and exogenous pathways.…”
Section: Cyps In the Brainmentioning
confidence: 97%
See 1 more Smart Citation
“…In human brain, membrane-bound CYP2D6 is localized in pyramidal cells of the cortex and hippocampus, as well as Purkinje cells of the cerebellum. CYP2D-mediated synthesis of dopamine from tyramine has recently been demonstrated to function in brain of the intact rat [61].…”
Section: Biogenic and Neurogenic Aminesmentioning
confidence: 99%